2016
DOI: 10.3233/cbm-160612
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Wilms tumor 1 mRNA expression levels in peripheral blood and bone marrow in patients with myelodysplastic syndromes

Abstract: Abstract.BACKGROUND: This present study was designed to follow up 82 patients among 115 MDS patients registered in study ODK-0801 for 5 years, to analyze the relationship between the WT1 mRNA expression level and prognosis. OBJECTIVE: This study aimed to investigate the clinical utility of WT1 mRNA expression levels. METHODS: After study ODK-0801, we investigated the conditions of the same patients once a year, including any clinical and laboratory findings supporting the diagnosis, and treatment among the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that WT1 mRNA expression can be a useful marker for diagnosis and risk evaluation of MDS . Therefore, we measured WT1 mRNA expression levels to evaluate disease progression during AZA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that WT1 mRNA expression can be a useful marker for diagnosis and risk evaluation of MDS . Therefore, we measured WT1 mRNA expression levels to evaluate disease progression during AZA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that WT1 mRNA expression can be a useful marker for diagnosis and risk evaluation of MDS. 17,18 Therefore, we measured WT1 mRNA expression levels to evaluate disease progression during AZA treatment. However, because there was no correlation between WT1 mRNA expression levels before treatment and therapy responses in the present study, WT1 may not be useful as a prediction marker for AZA response.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior work that has associated WT1 expression with poor prognosis in MDS and AML. [63][64][65][66] More novel was the association between shorter OS and CD93 hypomethylation in our cohort and overexpression in an external MDS cohort, because CD93 is a transmembrane receptor implicated in the pathogenesis of several malignancies. [67][68][69] The role of CD93 in myeloid malignancies is relatively unknown.…”
Section: Discussionmentioning
confidence: 95%
“…Kobayashi et al . found that elevated WT1 expression levels were also more prevalent in the high-risk group, as classified by IPSS-R categories [ 27 ]. In the different risk groups of MDS, high WT1 expression levels were 2 of 8 patients (25%), 10 of 29 (34.5%), 12 of 21 (57.1%), 9 of 11 (81.8%), and 11 of 13 (84.6%) in the very-low, low, intermediate, high, and very-high risk categories, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Kobayashi et al . [ 27 ] showed that the median OS of patients with WT1 mRNA expression levels of 500, 50000, 100000, 150000 copies were greater than 60.0, 45.0, 17.5 and 12.0 months, respectively. In the report of Nagasaki et al .…”
Section: Discussionmentioning
confidence: 99%